Energy Efficient Virtual Network Embedding In Federated Software Defined Networks - Dahir, Mohamed Haji; Alizadeh, Hadi; Gözüpek, Didem (IEEE, 2017)
In this paper, we focus on energy efficient virtual network embedding in federated (multi-domain) software defined networks (SDN), where a top (high-level) SDN controller manages the other SDN controllers, each of which is responsible the network management of its own domain. We propose a heuristic algorithm that performs virtual network embedding by aiming to minimize the total energy consumption of the network while at the same time adhering to the bandwidth requirements of the network links. Our proposed algorithm consists of three phases. In the first phase, the top SDN controller partitions the virtual network request into multiple domains, whereas in the second phase, each SDN controller implements virtual network embedding in its own domain and in the third phase, the algorithm performs interdomain routing. Our simulation results demonstrate that our proposed heuristic algorithm yields satisfactory solutions in terms of total energy consumption in comparison with a single domain scenario.
25th Signal Processing and Communications Applications Conference (SIU) -- MAY 15-18, 2017 -- Antalya, TURKEY
Keywords: Software defined networks; virtual network embedding; energy efficiency; green networks; multi-domain networks; heuristic algorithms